The Dynamics of Self-Understanding in Middle Adulthood Through Dream Analysis - Evelyn Deciana; Sri Mulyani Nasution (Penerbit Goodwood, 2026)
Purpose: This study aims to explore the process of self-understanding in middle adulthood through dream experiences from the perspective of analytical psychology.Research Methodology: This study employed a qualitative phenomenological design involving three Indonesian adults in middle adulthood who had experienced psychologically significant dreams and were able to reflect on their meanings. Data were collected through semi-structured interviews and written dream narratives and analysed using interpretative thematic analysis within the framework of analytical psychology.Results: The findings indicate that dream experiences contribute to an integrative process of self-understanding, including awareness of internal conflicts, the integration of rational and intuitive aspects, and a deeper understanding of interpersonal dynamics. Dreams also function as a reflective medium that facilitate emotional processing and psychological integration.Conclusions: Dream analysis may support the development of self-understanding by enabling individuals to access unconscious psychological dynamics and reflect more deeply on their subjective experiences. Limitations: This study was limited to a small number of participants and focused on subjective interpretations of dream experiences within a specific culture and psychological context.Contributions: This study extends the application of analytical psychology by demonstrating that dream analysis serves not only as a method of symbolic interpretation but also as a reflective process that facilitates self-understanding and psychological integration during middle adulthood.